2022
DOI: 10.1002/cnr2.1744
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of ABCB1, CDA, DCK, GSTT1, GSTM1 and outcomes in a cohort of pediatric acute myeloid leukemia patients from Colombia

Abstract: Background and Aim: Different studies have shown pharmacogenetic variants related to drug toxicity in acute myeloid leukemia (AML) patients. Our aim was to identify the association between ABCB1, CDA, DCK, GSTT1, and GSTM1 variants with clinical outcomes and toxicity in pediatric patients with AML.Methods: Fifty-one confirmed de novo AML pediatric patients were included. A SNaPshot™ assay and conventional PCR were used to evaluate ABCB1, CDA, DCK, GSTT1, and GSTM1 variants. Clinical outcomes and toxicity assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
1
0
3
Order By: Relevance
“…Constructing a haplotype with the ABCB1 rs1045642 and rs1128503 variants revealed an intriguing finding—the Chilean population exhibited the second lowest frequency for the AA haplotype among the populations analyzed ( Table 3 ). In a study involving Colombian children with acute myeloid leukemia (AML), the combination of ABCB1 rs1128503, rs2032582, and rs1045642 AA/AA/AA was strongly associated with death after hematopoietic stem cell transplantation, demonstrating an odds ratio of 13.73 [ 50 ]. Similarly, a study in Spanish adults with AML, assessing the same three ABCB1 variants, found that the haplotype containing A alleles was associated with higher post-induction mortality, increased nephrotoxicity, and hepatotoxicity [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Constructing a haplotype with the ABCB1 rs1045642 and rs1128503 variants revealed an intriguing finding—the Chilean population exhibited the second lowest frequency for the AA haplotype among the populations analyzed ( Table 3 ). In a study involving Colombian children with acute myeloid leukemia (AML), the combination of ABCB1 rs1128503, rs2032582, and rs1045642 AA/AA/AA was strongly associated with death after hematopoietic stem cell transplantation, demonstrating an odds ratio of 13.73 [ 50 ]. Similarly, a study in Spanish adults with AML, assessing the same three ABCB1 variants, found that the haplotype containing A alleles was associated with higher post-induction mortality, increased nephrotoxicity, and hepatotoxicity [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…У пациентов с «нулевым» генотипом риск развития кардиомиопатии был в 2,7 раза выше (ОШ 2,7; 95 % ДИ 1,3-5,9; p = 0,007) по сравнению с пациентами с положительным генотипом GSTM1 (-/ + или + / +) [35]. Статистически значимой корреляции между кардиотоксическими эффектами ХТ и вариантами генов SOD2 (rs4880), CAT (rs1001179), а также «нулевым» генотипом GSTT1 у больных ОЛЛ и ОМЛ не обнаружено [34,36].…”
Section: неходжкинская лимфомаunclassified
“…Ведущую роль в транспорте препаратов через плазматическую мембрану клеток играют АТФ-связывающие кассетные транспортеры (ABC-транспортеры), способные модулировать токсичность некоторых препаратов [46]. Как показали исследования, полиморфизмы генов ABC-транспортеров, включая ABCC1, ABCC2, ABCC5 и ABCB1, связаны как с повышенным риском развития сердечной недостаточности, так и с протективным действием при терапии антрациклинами у детей и взрослых с онкогематологическими заболеваниями [21,25,36,41,47,48].…”
Section: полиморфизмы генов метаболизма ксенобиотиковunclassified
See 1 more Smart Citation